Medical Imaging 2023: Image-Guided Procedures, Robotic Interventions, and Modeling 2023
DOI: 10.1117/12.2655257
|View full text |Cite
|
Sign up to set email alerts
|

Digital twin forecasting of microwave ablation via fat quantification image-to-grid computational methods

Abstract: Computational tools, such as "digital twin" modeling, are beginning to enable patient-specific surgical planning of ablative therapies to treat hepatocellular carcinoma. Digital twins models use patient functional data and biomarker imaging to build anatomically accurate models to forecast therapeutic outcomes through simulation, i.e., providing accurate information for guiding clinical decision-making. In microwave ablation (MWA), tissue-specific factors (e.g., tissue perfusion, material properties, disease s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For this determination, the average fat percentage (determined by mDIXON image analysis) across the entire liver (excluding vasculature) was calculated and then used within the context of Equation ( 7) to estimate the respective liver parenchymal material property. This approach reflects previous work in which it was found that the difference in therapy simulations was minima when comparing a homogeneous description versus a mapping of properties voxelby-voxel within the context of diffuse disease [48]. Given that the patients in this study presented with diffuse fatty liver disease, this approach was appropriate for the liver parenchyma.…”
Section: Constitutive Equations For Materials Properties D1 Mapping P...mentioning
confidence: 65%
See 3 more Smart Citations
“…For this determination, the average fat percentage (determined by mDIXON image analysis) across the entire liver (excluding vasculature) was calculated and then used within the context of Equation ( 7) to estimate the respective liver parenchymal material property. This approach reflects previous work in which it was found that the difference in therapy simulations was minima when comparing a homogeneous description versus a mapping of properties voxelby-voxel within the context of diffuse disease [48]. Given that the patients in this study presented with diffuse fatty liver disease, this approach was appropriate for the liver parenchyma.…”
Section: Constitutive Equations For Materials Properties D1 Mapping P...mentioning
confidence: 65%
“…In mDIXON imaging, the fat-to-water signal ratio establishes a fat fraction parameter, which represents the percentage of fat in a given volume of tissue [22] . The intensities of the fat fraction image were directly mapped into material properties and imported into the digital twin finite element model [47] . A material mixture equation to describe fat-dependent dielectric and thermal material properties is expressed as follows, \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} \begin{equation*} m\left( {f{\mathrm{\% }}} \right) = \left( {\left( {{m}_{liver} - {m}_{fat}} \right){e}^{ - {\tau }_k{\mathrm{*}}f{\mathrm{\% }}}} \right) + {m}_{fat}\ \tag{7} \end{equation*}\end{document} …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations